Normal acid-base balance in fetal capillary blood during labor and birth to the time of life - Bacini Colan, Javier (2015)
A study of acid-base balance in capillary blood Arterialized 30 term fetuses is presented during labor and time after birth. Each of the selected gestations has sibo considered normal considering maternal, fetal, labor factors, and dependent on the placenta, cord and newborn to rule out any pathology that could alter fetal acid-base balance and hence the newborn. To extract fetal capillary blood and newborn has followed the techniques proposed by Saling and Astrup.